Doxycycline induces apoptosis via ER stress selectively to cells with a cancer stem cell-like properties: importance of stem cell plasticity. (November 2017) - Matsumoto, Takashi; Uchiumi, Takeshi; Monji, Keisuke; Yagi, Mikako; Setoyama, Daiki; Amamoto, Rie; Matsushima, Yuichi; Shiota, Masaki; Eto, Masatoshi; Kang, Dongchon
Abstract Tumor heterogeneity can be traced back to a small subset of cancer stem cells (CSCs), which can be derived from a single stem cell and show chemoresistance. Recent studies showed that CSCs are sensitive to mitochondrial targeting antibiotics such as doxycycline. However, little is known about how cancer cells undergo sphere formation and how antibiotics inhibit CSC proliferation. Here we show that under sphere-forming assay conditions, prostate cancer cells acquired CSC-like properties: promoted mitochondrial respiratory chain activity, expression of characteristic CSC markers and resistance to anticancer agents. Furthermore, those CSC-like properties could reversibly change depending on the culture conditions, suggesting some kinds of CSCs have plasticity in tumor microenvironments. The sphere-forming cells (i.e. cancer stem-like cells) showed increased contact between mitochondria and mitochondrial associated-endoplasmic reticulum (ER) membranes (MAM). Mitochondrial targeting doxycycline induced activating transcription factor 4 (ATF4) mediated expression of ER stress response and led to p53-upregulated modulator of apoptosis (PUMA)-dependent apoptosis only in the cancer stem-like cells. We also found that doxycycline effectively suppressed the sphere formation in vitro and blocked CD44v9-expressing tumor growth in vivo. In summary, these data provide new molecular findings that monolayer cancer cells acquire CSC-like properties in a reversible manner. These findings provide important insights into CSC biology and a potential new treatment of targeting mitochondria dependency.